AATF/Che-1 RNA polymerase II binding protein overexpression reduces the anti-tumor NK-cell cytotoxicity through activating receptors modulation - Caforio, Matteo; Tumino, Nicola; Sorino, Cristina; Manni, Isabella; Di Giovenale, Stefano; Piaggio, Giulia; Iezzi, Simona; Strimpakos, Georgios; Mattei, Elisabetta; Moretta, Lorenzo; Fanciulli, M.; Vacca, Paola; et al. (Frontiers in Immunology, 2023)
AATF/Che-1 over-expression in different tumors is well known and its effect on tumorigenicity is mainly due to its central role demonstrated in the oncogenic pathways of solid tumors, where it controls proliferation and viability. The effect exerted by tumors overexpressing Che-1 on the immune response has not yet been investigated. Here we show that Che-1 is able to modulate the expression of Nectin-1 ligand at the transcriptional level, leading to the impairment of killing activity of NK-cells. Nectin-1 down-modulation induces a functional modification in NK-cell ligands expression able to interact with activating receptors and to stimulate NK-cell function. In addition, NK-cells from Che-1 transgenic mice, confirming a reduced expression of activating receptors, exhibit impaired activation and a preferential immature status. The critical equilibrium between NK-cell ligand expression on tumor cells and the interaction with NK-cell receptors is affected by Che-1 over-expression and partially restored by Che-1 interference. The evidence of Che-1-directed regulation of anti-tumor immunity supports the necessity to inhibit a target with a dual tumorigenic function as cancer promoter and immune response modulator.